2003
DOI: 10.1021/la0269210
|View full text |Cite
|
Sign up to set email alerts
|

Ion Fluxes to Channel Arrays in Monolayers. Computing the Variable Permeability from Currents

Abstract: Chronoamperometric currents arising from Tl + reduction at a Hg electrode covered with a phospholipid monolayer containing gramicidin monomer ion channels can be quantitatively understood as an interfacial permeation process with a variable local permeability. Any interfacial behavior (described by the permeability) can be combined with the properties of semi-infinite diffusion to yield a simple expression that allows: (a) the computation of the current corresponding to any given variation of the permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This way we found that with 3 tt in the range 1.4,.,2.0 k B T the monolayer is thermodynamically stable, where the observed zero-tension phase gradually transforms from the dense liquid (for lower values of 3 tt ) into gel-and liquid-crystal phases (for higher values). To exemplify, the average projected area per lipid is varying in the range, a xy ¼ 21,., 15 A 2 , which is reasonable for single-tail lipids 29,54 considering that the effective monomer size of 4…”
Section: Simulation Aspectsmentioning
confidence: 87%
See 2 more Smart Citations
“…This way we found that with 3 tt in the range 1.4,.,2.0 k B T the monolayer is thermodynamically stable, where the observed zero-tension phase gradually transforms from the dense liquid (for lower values of 3 tt ) into gel-and liquid-crystal phases (for higher values). To exemplify, the average projected area per lipid is varying in the range, a xy ¼ 21,., 15 A 2 , which is reasonable for single-tail lipids 29,54 considering that the effective monomer size of 4…”
Section: Simulation Aspectsmentioning
confidence: 87%
“…2,13,14,34 There exist also plausible theoretical (phenomenological) approaches to the problem. 10,[15][16][17] It remains, however, largely undetermined what type of transition is reflected by each peak in the C(V ) profile, 34 because such phenomenological hypotheses based on indirect observations cannot be easily verified in a supporting experiment that could reveal the resulting molecular (re-)arrangements. A better understanding and theoretical description in such cases requires further research, which can also be based on modelling with the aid of numerical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of electrochemical methods used to study diffusion may be applied to characterize transport in 0376 such films [15][16][17]. This approach has been used for studying diffusion in solids [17], Nafion [18], electropolymerized thin films [19,20] and in self-assembled lipid bilayers [21] and surfactant monolayers [22]. The present publication generalizes the approaches proposed earlier and adds some aspects important for relatively permeable and not entirely homogeneous thin films, such as the ones employed in polyamide RO/NF composites.…”
Section: Introductionmentioning
confidence: 99%
“…Although EIS experiments are run in a quasisteady-state mode whereby oscillations of voltage and current become reproducible, in fact it is an inherently non-steady-state technique that allows simultaneous analysis of many charge transfer phenomena on different time scales. The method gained much popularity in studies of coatings and corrosion on metals [23][24][25], self-assembled layers [21,22,26], polymer degradation [27], analytical chemistry [28], etc. A whole separate branch of EIS is studies of ion channels in biological and synthetic lipid membranes [21,29,30].…”
Section: Introductionmentioning
confidence: 99%